2013
DOI: 10.1017/s1352465813000313
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Effectiveness of Computer-Assisted Cognitive Remediation (CACR) in Adolescents with Psychosis or at High Risk of Psychosis

Abstract: CACR can be successfully administered in this population; it proved to be effective over and above CG for the most intensively trained cognitive ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 29 publications
(48 reference statements)
0
31
0
Order By: Relevance
“…Recent studies have suggested a positive effect of cognitive remediation in adolescents at risk for or affected by psychosis. 55,56 Research should also consider whether psychotherapeutic interventions, which are specifically designed for abused and neglected children 57 and which already address trauma consequences, such as dissociation, disorganized attachment and distorted attributions/mentalization, could normalize the cognitive risk trajectory.…”
Section: Visual Episodic Memorymentioning
confidence: 99%
“…Recent studies have suggested a positive effect of cognitive remediation in adolescents at risk for or affected by psychosis. 55,56 Research should also consider whether psychotherapeutic interventions, which are specifically designed for abused and neglected children 57 and which already address trauma consequences, such as dissociation, disorganized attachment and distorted attributions/mentalization, could normalize the cognitive risk trajectory.…”
Section: Visual Episodic Memorymentioning
confidence: 99%
“…Significant improvements have been reported in attention, memory, problem solving ability, and global cognition (Kern et al, 2009; Wykes et al, 2011). Recent studies suggest that CR is beneficial for early-course vs. long-term (Bowie et al, 2014) patients and adolescents with early-onset schizophrenia (Holzer et al, 2014; Puig, 2014; Ueland and Rund, 2005; Wykes et al, 2007). Studies of successful CR programs support the feasibility of utilizing computer-based interventions with both adult (Kurtz et al, 2007) and adolescent populations (Holzer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that CR is beneficial for early-course vs. long-term (Bowie et al, 2014) patients and adolescents with early-onset schizophrenia (Holzer et al, 2014; Puig, 2014; Ueland and Rund, 2005; Wykes et al, 2007). Studies of successful CR programs support the feasibility of utilizing computer-based interventions with both adult (Kurtz et al, 2007) and adolescent populations (Holzer et al, 2014). Current studies have successfully employed a remote, computer based CR program for stable patients (Ventura et al, 2013) and younger individuals (Fisher et al, 2015) with recent onset psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…154, 160, 166-169 Building on demonstrated efficacy with established illness, CR with PR has used established computerized cognitive remediation programs like COGPACK, Lumosity, or PositScience . 170,171 These programs provide training in cognitive domains such as attention, speed of processing, executive function, learning and memory, and social perception.…”
Section: Intervening In Psychosis Riskmentioning
confidence: 99%